Analisis Iklim Ekstrim Untuk Deteksi Perubahan Iklim Di Sumatera Barat - Sugeng Nugroho (School of Postgraduate Studies, Diponegoro Univer, 2019)
Significant consequences of global warming due to climate change, which is characterized by increasing extremes of climate events, both magnitude and frequency. Climate change that occurs in an area is highly dependent on the sensitivity of local factors in responding to global climate change that occurred. The research was conducted in West Sumatera region which was divided into two parts of topography, lowland and highlands, using observation data and model data. The extreme climate index is determined by using the ETCCDI standard. Climate change is also seen from the shift in climate patterns within a predetermined period of time. The significance of extreme climatic trends and climate change is done by the Mann-Kendall test. The result of the analysis shows that in general there has been an increase in air temperature in the research area, both in highland and lowland areas there is a tendency to increase extreme rainfall in highland areas, while for lowland areas tend to experience a negative trend. Trend test results show that not all variations of extreme climate index trends are significant on significance tests at 90% and 95% or more confidence levels and there is also no difference in extreme climatic conditions between lowland and upland areas. Temperature pattern shift of 0.5 to 1.0 OC in both low and high areas of research. As for the pattern of rain occurred shift with lower average for in lowland area of research area and tendency of increasing amount of rainfall in highland area of research area.